A case of Klinefelter syndrome with hypersexual desire. (29th August 2017) - Okolie, Kingsley; Perampalam, Sumathy; Barker, Anthony; Nolan, Christopher J
Abstract : Klinefelter syndrome (KS) is a chromosomal disorder affecting males, with the typical karyotype of 47, XXY due to a supernumerary X chromosome, which causes progressive testicular failure resulting in androgen deficiency and infertility. Despite it being the most common sex chromosomal disorder, its diagnosis is easily missed. In addition to its classical clinical features of tall stature, gynaecomastia, small testes, and symptoms and signs of hypogonadism including infertility, KS is also often associated with neurocognitive, behavioural and psychiatric disorders. We present a 44-year-old man with KS who, despite having erectile dysfunction, paradoxically had increased libido. He used sildenafil to overcome his erectile dysfunction. Hypersexuality was manifested by very frequent masturbation, multiple sexual partners most of whom were casual, and a sexual offence conviction at the age of 17 years. Discussion focuses on the frequent failure of clinicians to diagnose KS, the neurocognitive, behavioural and psychiatric aspects of KS, this unusual presentation of hypersexuality in a man with KS, and the challenges of medical management of hypogonadism in a man with a history of a sexual offence. Learning points: Klinefelter syndrome (KS) is common in men (about 1 in 600 males), but the diagnosis is very often missed. In addition to classic features of hypogonadism, patients with KS can often have associated neurocognitive, behavioural and/or psychiatric disorders. More awareness of the association between KS and difficulties related to verbal skills in boys could improve rates of early diagnosis and prevent longer-term psychosocial disability. Hypersexuality in the context of hypogonadism raises the possibility of sex steroid independent mechanistic pathways for libido. Testosterone replacement therapy in KS with hypersexuality should be undertaken with caution using a multidisciplinary team approach.